Availability of steam impacts coke properties in steam reforming of acetic acid. (8th February 2021) - Li, Xianglin; Zhang, Zhanming; Zhang, Lijun; Gao, Guanggang; Wei, Tao; Zhang, Zehui; Zhang, Shu; Chen, Guozhu; Li, Cuncheng; Hu, Xun
Abstract: Steam to carbon ratio (S/C) determines the availability of oxygen-containing species during steam reforming, which not only affect the amount of coke formed, but also might impact physicochemical properties of the coke generated. In this study, the effect of S/C on the coke formation in steam reforming of acetic acid was assessed. The results indicated that dissociative absorption of acetic acid generated the intermediates containing both CO and CC groups even at 100 °C. At low S/C, the insufficient ∗OH reacted with carbonaceous intermediates such as CHx to form more carbonyl species, leading to significant coking and lower gas yields. Sufficient ∗OH at high S/C facilitated transformation of the carbonyl-containing species into gases, minimizing coking. The varied amount of coke showed significant effect on the diffraction of metallic nickel phase, the particle size of Ni and the absorption for the Si–O–Si functional groups on spent catalysts. The coke formed at low S/C was more aromatic with high thermal stabilities, while the coke formed at high S/C was more aliphatic with low thermal stabilities. The involvement ∗OH species in coking process determined not only properties but also morphologies of the coke. The coke formed at low S/C showed bamboo-like, dendritic or twisted rope-like structure. While the higher S/C favored the generation of the carbon nanotubes with smooth outer surface. Graphical abstract: Image 1 Highlights: S/C affects both amount and property of coke formed in acetic acid reforming. More CO is formed via reaction between ∗OH and ∗Cx Hy, but is gasified at high S/C. More coke forms at low S/C, while small amount of steam changes properties of coke. Coke formed at low S/C is more aromatic with higher stability than that at high S/C. Coke of dendritic bamboo or twisted rope-like structure relates to ∗OH abundance.